2008
DOI: 10.1152/advan.00067.2007
|View full text |Cite
|
Sign up to set email alerts
|

IT-based activity in physiology education: an experience from a developing country

Abstract: Information technology (IT)-based components are included as active learning activities in medical curricula that have been shown to be more effective than most passive learning activities. In developing countries, these activities are not popular compared with developed countries. In this study, an IT-based assignment was carried out in physiology for undergraduates in Sri Lanka. We assessed certain basic IT capabilities before the assignment and found that the capability of using MS Word, e-mail, and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…These reports suggested that the implementation of Moodle was generally well accepted by the students as a supplement to traditional methods of teaching and has made an effective contribution to the teaching and learning process, including an improvement in student grades (7). Although a number of studies have shared their experiences on using customized web-based learning activities in the teaching of first-year medical physiology course (8,9,20), there is still a paucity of literature exploring successful models of how physiology educators can integrate readily available CMSs such as Moodle into their existing curriculum. This issue is pertinent as most medical educators have neither the required funds nor necessary computer skills to design a comprehensive web-based learning system for their students.…”
mentioning
confidence: 99%
“…These reports suggested that the implementation of Moodle was generally well accepted by the students as a supplement to traditional methods of teaching and has made an effective contribution to the teaching and learning process, including an improvement in student grades (7). Although a number of studies have shared their experiences on using customized web-based learning activities in the teaching of first-year medical physiology course (8,9,20), there is still a paucity of literature exploring successful models of how physiology educators can integrate readily available CMSs such as Moodle into their existing curriculum. This issue is pertinent as most medical educators have neither the required funds nor necessary computer skills to design a comprehensive web-based learning system for their students.…”
mentioning
confidence: 99%
“…For instance, in Sri Lanka, IT based components are not included in medical curricula in most medical schools, and experiences with IT-based activities in medical schools are limited. The case is the same for most developing countries, and publications on this topic from those countries are limited [11].…”
Section: Ict-based Instructional Strategies In Medical Collegesmentioning
confidence: 99%
“…Previous ICT based activities introduced in the undergraduate curriculum in the Faculty of Medicine, University of Ruhuna have had mixed results (1,2) . One reason for failure was poor ICT skills of the undergraduates (3) .…”
Section: Introductionmentioning
confidence: 99%